Inhibition of Host-Cell Protein and Ribonucleic Acid Synthesis by Newcastle Disease Virus - Wilson, D. E. (1968)
The mechanisms of Newcastle disease virus-(NDV) induced inhibition of cell protein and ribonucleic acid (RNA) synthesis were investigated. It was observed that the ability of NDV to inhibit cell RNA synthesis is dependent on the virus strain. The inhibitors, azauridine and cycloheximide, were added to cell cultures at different times after infection to study the roles of protein and RNA synthesis in the viral inhibition process. Viral inhibition of cell RNA synthesis and viral inhibition of cell protein synthesis become resistant to cycloheximide at a different time after infection than that in which they become resistant to azauridine. The results indicate that the inhibition of cell RNA synthesis by the Texas strain involves the synthesis of inhibitory proteins which are coded by the viral genome. The Texas and Beaudette strains of NDV appear to employ different mechanisms for the inhibition of host-cell protein synthesis. Viral inhibition of cell protein synthesis does not appear to cause, or be the result of, viral inhibition of cell RNA synthesis.